The Mindset is the Message: Reflections on the Mindset Propagated by Respective Instagram Accounts - Maja Jerrentrup (Recent Trends in Arts and Social Studies Vol. 4, 2023)
Nowadays, the “mindset” seems to be a marketable commodity and–like anything trending–is very present on social media. Still, unlike #bodypositivity, for example, the term has not yet received much scholarly attention. This article aims at understanding which type of mindset social media advocate for and what means are chosen to articulate this. After giving an emic definition and categorizing the values communicated in a sample of Instagram posts, two findings become salient: Inconsistencies and gender bias. Because of contradictory messages, for the recipient, the unpleasant feeling of cognitive dissonance should arise–independence from other people is stressed, but also empathy and changing perspectives. Control is demanded but also giving up control etc. Mixed and contradictory messages are shared not only by different accounts but also by individual accounts. These inconsistencies can be related to Instagram’s design, which constantly offers inputs and requires flexibility and a change of perspective. In addition, the imagined community with other recipients can be defined as a core value: all recipients process fundamental human experiences such as rejection, failure, and loneliness. Although many messages stress independence, on a fundamental level, it is about connection. The second finding concerns the photographs: if people are depicted, they are almost exclusively men, although it is unclear whether the target group is male. There is some evidence that this is due to gender-specific vocabulary, but it could also be interpreted as women or transgender individuals being less apt to reflect the mindset idea in the perception of account holders.